Effect of the disposal of coffee wet milling residues on the physical and chemical characteristics of natural flowing water - Ruiz-Nájera, Ramiro Eleazar; Medina-Meléndez, José Alfredo; Carmona-de la Torre, Jesús; Rincón-Enriquez, Gabriel; Sánchez-Yáñez, Juan Manuel; Raj-Aryal, Deb (REVISTA TERRA LATINOAMERICANA, 2021)
Coffee wet milling is a process that demands large quantities of water, and produces mucilage and pulp that are discharged into surface water. The objective of this study was to analyze the physical and chemical properties of the water in Cuxtepec and Cabañas rivers in the municipality of Concordia, Chiapas, Mexico. In these water masses, coffee wet milling subproducts are discharged during the harvest. Sampling sites were San Pedro stream, Cabañas river, rancheria 30 de Agosto and Cuxtepec river. Water samples were obtained in October and December, 2016, and January, April and June, 2017. The following parameters were determined: pH, electrical conductivity (EC), total dissolved solids (TDS), total suspended solids (TSS), sedimentable solids (SS), chemical oxygen demand (COD), biochemical oxygen demand (BOD), total nitrogen (TN), ammonia (NH4), total phosphorus (TP), water hardness (WH), water temperature (WT), and air temperature (AT). COD and BOD content varied from site to site, with maximum values of 7.7 and 1.25 mg L-1, respectively. This low concentration allowed for high oxygen level (7.99 mg L-1). The TDS load was 149.7 mg L-1 and pH was 8.9, indicating favorable conditions for aquatic life. In general, the values measured in groundwater under traditional coffee wet milling plants did not show levels that indicate risks for agricultural use or for consumption by animals and people inhabiting areas close to the water bodies in the region. These findings suggest a need to establish a contaminant monitoring system for the coffee-producing regions of Chiapas, and improve ecological management of residual waters produced by coffee wet milling according to pollutant concentrations.